circATP2B1 Promotes Aerobic Glycolysis in Gastric Cancer Cells Through Regulation of the miR-326 Gene Cluster - Zhao, Xihe; Tian, Zhong; Liu, Lei (Frontiers in Oncology, 2021)
The discovery of circular RNA (circRNA) enormously complimented the repertoire of traditional gene expression theory. As a type of endogenous noncoding RNA, circRNA participates in the occurrence of many kinds of tumors in addition to regulating their development. The Warburg effect (aerobic glycolysis is taken with priority for cancer cells instead of oxidative phosphorylation) is one of the most important factors involved in the excessive proliferation of gastric cancer cells. Our data showed that circRNA circATP2B1 (also called hsa_circ_000826) was overexpressed in gastric cancer tissues instead of linear ATP2B1 mRNA, and it promoted aerobic glycolysis in gastric cancer cells. Bioinformatic Gene Ontology analysis showed that the potential downstream targets of circATP2B1 include the microRNA miR-326 gene cluster (miR-326-3p/miR-330-5p), which is functionally focused on cell growth and metabolic processes. The expressions of miR-326-3p/miR-330-5p were downregulated in gastric cancer, and circATP2B1 functionally targeted miR-326-3p/miR-330-5p in an RNA-induced silencing complex (RISC) dependent manner. Dual-luciferase reporter assays demonstrated that pyruvate kinase M2 (PKM2) was one of the targets of miR-326-3p/miR-330-5p. As a rate-limiting enzyme in the aerobic glycolytic pathway, PKM2 accelerated gastric cancer cells’ glucose uptake and increased cell viability. Taken together, circATP2B1 captured miR-326-3p/miR-330-5p and decreased the suppression of PKM2 by miR-326-3p/miR-330-5p, thus aiding the aerobic glycolysis and proliferation of gastric cancer cells. This study identified a novel molecular pathway in gastric cancer that may provide more targets for reversing cancer metabolic reprogramming, as well as a potential strategy for targeted therapy of gastric cancer.